2006
DOI: 10.12702/1984-7033.v06n02a02
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of combining ability in soybean cultivars

Abstract: Eight soybean cultivars (Doko, Bossier, Savana, Paraná and Cristalina) were crossed in a diallel design. Plants of the F 1 generation and their parents were evaluated under short-day conditions for the determination of the general (GCA) and specific (SCA) combining ability. The estimated GCA and SCA values were significant for the evaluated traits except for the "total cycle". Highest GCA effects for the traits "days to flowering", "plant height", "insertion height", "number of branches" and "total cycle" wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
4
8
0
1
Order By: Relevance
“…The highly significant GCA and SCA for duration to maturity (P<0.01) suggested that both the additive and non-additive gene action was important in determination of this trait. Similar results were reported by Srivastava et al (1978), Limproongratna and Maneephong (1979), Tukamuhabwa et al (2002), Agrawal et al (2005), Gavioli et al (2006) and Sher et al (2012). GCA/SCA ratio close to zero suggested that non-additive gene effects played a bigger role than additive gene effects.…”
Section: Agronomic Traitssupporting
confidence: 85%
See 3 more Smart Citations
“…The highly significant GCA and SCA for duration to maturity (P<0.01) suggested that both the additive and non-additive gene action was important in determination of this trait. Similar results were reported by Srivastava et al (1978), Limproongratna and Maneephong (1979), Tukamuhabwa et al (2002), Agrawal et al (2005), Gavioli et al (2006) and Sher et al (2012). GCA/SCA ratio close to zero suggested that non-additive gene effects played a bigger role than additive gene effects.…”
Section: Agronomic Traitssupporting
confidence: 85%
“…Parental genotypes were generally taller (33.3 cm) compared to their F1 progenies (31.2 cm). These findings were in agreement with Sharma (2004); Wanderi (2012); Karyawati et al (2015) but were not in agreement with Gavioli et al (2006) who found progenies to be more taller than parents. Genes that control the plant height in parents could be recessive.…”
Section: Agronomic Traitssupporting
confidence: 82%
See 2 more Smart Citations
“…The relative importance of general and specific combining ability on progeny performance was estimated based on the Baker's Ratio (1978) and it showed a preponderance of additive gene effects in the inheritance of all traits except grain yield and root lodging. Thus, the response of hybrids to these agronomic traits could be predicted based on the GCA of the parents (Gavioli et al, 2006). Thus, the additive effects could be exploited in the introgression of the yield related traits leading to enhance gains from selection (Sese et al, 2002).…”
Section: Discussionmentioning
confidence: 99%